Participation Constraints in the Stock Market: Evidence from Unexpected Inheritance Due to Sudden Death - Andersen, Steffen; Nielsen, Kasper Meisner (Review of Financial Studies, 2011)
[We use a natural experiment to investigate the impact of participation constraints on individuals' decisions to invest in the stock market. Unexpected inheritance due to sudden deaths results in exogenous variation in financial wealth, and allows us to examine whether fixed entry and ongoing participation costs cause non-participation. We have three key findings. First, windfall wealth has a positive effect on participation. Second, the majority of households do not react to sizeable windfalls by entering the stock market, but hold on to substantial safe assets—even over longer horizons. Third, the majority of households inheriting stock holdings actively sell the entire portfolio. Overall, these findings suggest that participation by many individuals is unlikely to be constrained by financial participation costs.]